2016
DOI: 10.1177/1533317516650806
|View full text |Cite
|
Sign up to set email alerts
|

Ecopsychosocial Interventions in Cognitive Decline and Dementia

Abstract: Dementia is a major medical and social scourge. Neither pharmacological nor nonpharmacological interventions and treatments have received sufficient funding to be meaningful in combatting this tsunami. Because the term-"nonpharmacological"-refers to what these interventions are not, rather than what they are, nonpharmacological treatments face a special set of challenges to be recognized, accepted, funded, and implemented. In some ways, the current situation is analogous to using the term "nonhate" to mean "lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Although the scope of this paper was not a systematic review of the literature, the broad expertise of the INTERDEM Social Health Taskforce members, their different professional and cultural backgrounds, and the methodology followed to achieve the aims of this position paper, which also included a consultation of people with dementia through the EWGPWD, resulted in a broad and rich overview of the state of knowledge regarding social health in dementia. We are aware, though, that as the focus of the article was limited to the operationalization of the concept of social health as described by Huber et al 2011, we did not discuss relevant new related models on health in Alzheimer's disease, such as the eco-psychosocial model (Whitehouse, 2014;Zeisel, Reisberg, Whitehouse, Woods, & Verheul, 2016). Some caution is indicated regarding generalization of the concept of social health.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Although the scope of this paper was not a systematic review of the literature, the broad expertise of the INTERDEM Social Health Taskforce members, their different professional and cultural backgrounds, and the methodology followed to achieve the aims of this position paper, which also included a consultation of people with dementia through the EWGPWD, resulted in a broad and rich overview of the state of knowledge regarding social health in dementia. We are aware, though, that as the focus of the article was limited to the operationalization of the concept of social health as described by Huber et al 2011, we did not discuss relevant new related models on health in Alzheimer's disease, such as the eco-psychosocial model (Whitehouse, 2014;Zeisel, Reisberg, Whitehouse, Woods, & Verheul, 2016). Some caution is indicated regarding generalization of the concept of social health.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…15 of the caregiving system, remains important and has been reconceptualised from 'non-pharmacological' interventions to 'ecopsychosocial' interventions. 331 The ResCare studies concluded that the care home industry in England was perhaps not yet ready to fully embrace an infrastructure comprising computerised learning or an IMS for decision-making about the management of CB in dementia (see Chapters 3 and 4). However, the potential for better uptake of e-learning in smaller care homes with less hierarchical leadership and support from the equivalent of an external supervisor, such as trained dementia therapist, may have potential (see Chapter 4).…”
Section: Discussion: the Management Of Challenging Behaviour In Dementiamentioning
confidence: 99%
“…Some psychosocial interventions may be described by a clear manual but for complex interventions of a person-centered, relational, psychotherapeutic and/or ecopsychosocial nature, it is highly challenging to narrow down actions and responses in a serial order of events and capture simple interconnections between them. [6][7][8] The level of complexity increases further when interventions are not a planned session-based service, but an interaction intended to be implemented as required or PRN (pro re nata. From Latin, meaning in the circumstances or as the circumstance arises.)…”
Section: Introductionmentioning
confidence: 99%